The social meaning of money in social interaction of boarding students - Romi Mesra; Erianjoni Erianjoni; Fitri Eriyanti (Fakultas Ilmu Pendidikan UNP)
The purpose of this research are to reveal social symbols of money, identify the symbolic meaning of money, and explain the social impact of money among boarding students, as well as disclosed by Weber (1978) seeing money is the most perfect means for economic and social transactions. Various studies relating to the meaning of money that has been done previously did not elaborate in depth about it. This researh used mixed method by using interview technique conducted with 79 college boarding house student, boarding owner, societies, local official goverment as informants of this study, the quetionaries shared for 69 of college boarding students and observation. The result of this research: social symbol of money are life style, clothes, community, boarding house, university, hangout, vehicle, food, and crisis month. The symbolic meaning of money are there is money there is friend, there are no problem cannot be solved by money, money is instrument; (money is an instrument to join a community, to have fun, and to doing mobility), money is god, money is a goal, money is life. Positive impact of money are to make easy to do mobility and to fullfil life necessaries. Negatif impacts of money are having fake friend, causing debt, and conflict. Financial management are saving money on ATM, avoiding buyin un-necessary things, deposite to the owner of boarding house, and scheduling remittances.